Assessing The Influence Of Pandrah Irrigation System Performance Indicators Using Structural Equation Modeling - Azmeri Azmeri; Winardi Winardi; Faris Zahran Jemi (Aceh International Journal of Science and Technology, 2020)
Pandrah Weir, built-in 1987, serves the Pandrah Technical Irrigation Area in Bireuen District, Aceh Province, with an area of 1.203 Ha. Its old infrastructure has experienced various damage that can decrease the irrigation system performance. The Pandrah irrigation system's previous performance assessment by both the MASSCOTE approach and Rapid Appraisal Procedure (RAP) evaluation suggested a service level of 3.05 (useful classification). This study assessed the effect of the variables on the Pandrah irrigation system's performance with Structural Equation Modeling (SEM) operated by the AMOS program. The four leading indicators were irrigation service, Water User Farmers Association (P3A), operator Human Resources (H.R.), and irrigation operation modernization. The refinement of irrigation system performance analysis using SEM showed that results of the four irrigation system performance indicators, namely: 0.082 (p=0.768), 0.090 (p=0.273), 0.419 (p=0.287), and 0.606 (p=0.039) for irrigation service, P3A indicator, irrigation operation modernization, and H.R. respectively. Based on the evaluation of the four indicators of irrigation system performance, it is concluded that the Pandrah irrigation system's performance is good. This performance assessment provides a clear picture of irrigation water services, H.R., P3A being an initial assessment for priorities, planning, and scheduling to start modernization programs for irrigation system operations. Irrigation modernization aims to facilitate the operation and maintenance by improving the irrigation system. This modernization means that irrigation planning, irrigation operation, maintenance, and monitoring systems have been carefully calculated before proposing a new irrigation network. The success of monitoring activities requires the use of information technology.